A decade of transcription factor-mediated reprogramming to pluripotency - Takahashi, Kazutoshi; Yamanaka, Shinya (Nature reviews. Molecular cell biology, 2016)
This year marks the tenth anniversary of the generation of induced pluripotent stem cells (iPSCs) by transcription factor-mediated somatic cell reprogramming. Takahashi and Yamanaka portray the path towards this ground-breaking discovery and discuss how, since then, research has focused on understanding the mechanisms underlying iPSC generation and on translating such advances to the clinic. The past 10 years have seen great advances in our ability to manipulate cell fate, including the induction of pluripotency in vitro to generate induced pluripotent stem cells (iPSCs). This process proved to be remarkably simple from a technical perspective, only needing the host cell and a defined cocktail of transcription factors, with four factors — octamer-binding protein 3/4 (OCT3/4), SOX2, Krüppel-like factor 4 (KLF4) and MYC (collectively referred to as OSKM) — initially used. The mechanisms underlying transcription factor-mediated reprogramming are still poorly understood; however, several mechanistic insights have recently been obtained. Recent years have also brought significant progress in increasing the efficiency of this technique, making it more amenable to applications in the fields of regenerative medicine, disease modelling and drug discovery.